Studi Perbandingan : Beban Kerja Perawat Isolasi Covid19 di Rumah Sakit dr. Rasidin Padang dan Rumah Sakit Ibnu Sina Padang - Sri Ameliati; Yulastri Arif; Esthika Ariany Maisa (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The workload experienced by health workers, especially nurses, occurs because of anxiety about the high risk of disease transmission, the increasing number of cases of the spread of Covid-19 and confirmed Covid-19 patients, the lack of human resources for hospitals so that the services provided are not optimal, coupled with high work pressure. , unclear task and role conflict. The purpose of this study was to compare the Covid 19 Isolation Nurse Workload in 2 hospitals, namely RSUD dr.Rasidin and RS Ibnu Sina Padang. The research design is descriptive quantitative with cross sectional method. The sample in the study was 66 nurses at dr.Rasidin Hospital and at Ibnu Sina Hospital Padang with 55 nurses. The research instrument used a questionnaire. Data collection with frequency distribution analysis, independent t test and one way ANOVA. The results showed that the t value (2.490) > t table 1.657) or the sig value (0.014) < 0.05, so there was a difference in the workload of the Covid 19 isolation nurse at Dr. Rasidin Hospital Padang and Ibnu Sina Hospital Padang. Based on the results of this study, it is expected that the hospital will pay more attention to and maintain every situation and condition when providing nursing care services during the COVID-19 pandemic by paying attention to all aspects related to workload, psychological conditions, physical tasks, organization and work environment.